Intervention Strategy against Abrasion within the Framework of Coastal Management in Paojepe, Wajo, South Sulawesi - Soehardjono Soehardjono; Y. Purwanto (The Ethnobiological Society of Indonesia, 2004)
The study conducted in 1999 2001 has aimed to solve the abrasion problem at Paojepe coast, Wajo, South Sulawesi. This study has elucidated some research findings. Firstly, the damage of the coastal environment in Paojepe has reached such a critical stage that it urgently calls for measures to address and overcome the problems. The undeniable fact under discussion here includes depletion of the mangrove forest, rapid coastal abrasion, and decrease in the coastal biodiversity. Secondly, the critical condition of the coast still be solved through three main approaches : (1) biological approach : Rbkophoni spp., and mangrove species replantation ; (2) physical approach : adaptative strategy using wave breaker and log-blocker construction ; and (3) effort to increase the roles of the community. Partial approach to the handling of abrasion (for example, by only focusing on biological or physical aspect) is unlikely to lead to success or produce satisfactory results. A few cases of abrasion handling through mangrove planting without taking into account the physical aspects (oceanography) and socio-cultural conditions of the local people have ended in complete failure. Careful development and thorough examination of an approach, coupled with interdisciplinary methodology embracing various aspects (socio-cultural, physical, ecological, etc), will lead to positive results and success. Each aspect has its own mutually exclusive and mutually supportive a role. The Rhizopbora planting activities on the coast of Paojepe have run well without significant technical problem. Growth and development of the Rhizophora have been satisfactory; with more than 90 O/ seedlings surviving. At three years old, the Rbizophora has been 2.5 to 3 meters high and start producing several fruit even a few At about three and a half years old, they will have developed strong roots, but still need some time before they can withstand the harsh waves. A study under LIPI concludes that under normal circumstances, mangroves will be strong enough against abrasion at the age of 5 years. However, it also depends on the physical aspects of the coast (i.e. structure and texture of the soil), and on oceanographical aspects. The other strateges against abrasion will be discussed completely in this article.